2009
DOI: 10.1007/s00330-009-1436-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of a consultant radiologist—are patients still in the dark?

Abstract: Little is known regarding public awareness of the roles and responsibilities of a consultant radiologist. Between 1 April and 20 May 2008, 916 outpatients attending our radiology department completed a questionnaire addressing this issue. We found public perception variable. Thirty-six percent of respondents thought we were responsible for choosing appropriate imaging; only 65% perceived that we reported studies. Another 38% felt that we did not play an important role in their treatment, and 38% considered tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
5
10
2
Order By: Relevance
“…This finding is in line with results from the aforementioned study by Grant et al [6]. In their study, 53% of participants thought that radiologists performed their examination.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is in line with results from the aforementioned study by Grant et al [6]. In their study, 53% of participants thought that radiologists performed their examination.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is at odds with the results of a study carried out by Grant et al [6], who found that the majority of their respondents (82%) could identify that radiologists were medically qualified. 54% of their study participants related the length of time spent training as a radiologist to the complexity of the role of the radiologist.…”
Section: Discussioncontrasting
confidence: 64%
“…We also surveyed our respondents regarding their knowledge of radiologists. In agreement with previous studies [11,13,14], there was a general lack of knowledge among patients regarding the education and role of radiologists. It is possible that this misunderstanding is a contributor to patients' disinterest in hearing results from radiologists, as suggested by our subanalysis showing slightly more interest in radiologist-centric communication models among patients most familiar with radiologists' role.…”
Section: Journal Of the American College Of Radiology 559supporting
confidence: 90%
“…First among these unknowns are the preferences of patients. Few studies have examined patients' preferences, and those that have, have yielded conflicting results [8][9][10][11][12][13]. Additionally, most previously published studies involved surveys of outpatients at single institutions, resulting in narrowly selected groups of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that patients prefer to receive their test results from RPs rather than radiologists (2,(20)(21)(22)(23). However, the results of these studies should be interpreted cautiously because they do not involve a standardized method of conduct that includes factors such as the patients' educational and sociocultural background; anticipated delivery time of the test results; and the type of patient-radiologist encounter (i.e., interactive vs. noninteractive).…”
Section: Discussionmentioning
confidence: 99%